ABORTION DUE TO ADVENTITIOUS PLACENTATION IN A JERSEY CROSSBRED CATTLE - RAJA, S; VIJAYARAJAN, A; PRABAHARAN, V; JAYAGANTHAN, P; SIVAKUMAR, A; SATHESH KUMAR, S (The Indian Journal of Animal Reproduction, 2016)
A four month pregnant pleuriparous Jersey crossbred cattle was presented with vaginal discharge and lodgingof fetus in cervix. By manual traction and lubrication aborted male fetus was delivered along with placenta thatwas adventitious in nature.
Keywords: Abortion; Adventitious Placenta; Cattle; Jersey